Gestational - age - specific reference intervals for blood pressure in normal pregnancy in a Southern Chinese population - Yuguo Deng; Lanfang Liang; Ying Gao; Guilian Liao; Qiaozhu Chen; Zijian Huang; Jinying Yang (BMC Pregnancy and Childbirth)
Abstract Objective Physiological blood pressure changes in pregnancy are insufficiently defined. This paper describes the blood pressure changes across healthy pregnancies in a Southern Chinese population to present gestational - age - specific blood pressure ranges with smoothed centiles (3rd, 10th, 50th, 90th, and 97th). Methods Antenatal blood pressure measurements [median (interquartile range) 9 (8 - 10) per woman] were repeated in 17, 776 women from a Southern China population. Multilevel cubic splines models were used to derive longitudinal reference ranges for systolic blood pressure (SBP) and diastolic blood pressure (DBP) from 6 to 42 weeks of gestation for the normal pregnancies (excluding chronic hypertension, preeclampsia, diabetic ones, and preterm birth et al.). Results Systolic and diastolic BP increased from 6 weeks of gestation: 50th centile (3rd - 97th centile) 106 (87 - 125); 61 (47 - 77) mm Hg to 12 weeks of gestation: 50th centile (3rd - 97th centile) 108 (88 - 129); 64 (49 - 81) mm Hg. Then, the lowest value of 107 (87 - 129); 62 (47 - 78) mm Hg was reached at 16 weeks and 20 weeks of gestation, respectively. Systolic and diastolic BP then rose to a maximum median (3rd - 97th centile) of 115 (96 - 135); 68 (53 - 85) mm Hg at 42 weeks of gestation. Additionally, the ascending tendency of SBP after 16 weeks of gestation was interrupted by two fluctuations that occurred at 24 weeks and 30 weeks of gestation. Conclusions In summary, our study provides blood pressure reference values for Southern Chinese women with normal pregnancies. To identify gestational hypertension and hypotension, centiles for gestational - age - specific BP should be defined in healthy pregnancies. Understanding these changes in low risk pregnancies is essential to optimize maternal blood pressure management.